MULTIPARAMETRIC MRI DIAGNOSIS OF SOFT TISSUE TUMORS. (Лучшие интеллектуальные исследования, 2025)
Abstract: The purpose of the study. To evaluate multiparametric MRI for differentiation of benign and malignant soft tissue tumors.